Research on trace minerals in common bean - Beebe, Steve E.; Gonzalez, Alma Viviana; Rengifo, Judith (International Food Policy Research Institute, 1999)
Food legumes in general contain appreciable quantities of iron and other minerals. Although legumes are often cited as a complement to cereals in terms of amino acid content, they also make a particularly important contribution to micronutrient nutrition. Decreasing legume per capita consumption in India is considered to be one possible cause of increasing iron deficiency, illustrating the importance of legumes in the diet. The common bean (Phaseolus vulgaris L.) is the most important grain legume for direct human consumption, being especially important in Eastern Africa and Latin America. CIAT has participated in the DANIDA funded project on micronutrients in an attempt to assess the feasibility of improving common beans for micronutrient content, especially iron and zinc.